PHYSIOLOGICAL AND BEHAVIOURAL DYNAMICS OF INDO-PACIFIC BOTTLENOSE DOLPHINS DURING THE PROCESS OF TRANSFER, ADAPTATION, AND ENVIRONMENTAL ENRICHMENT IN A NEW EX-SITU HABITAT - Ida Bagus Nararya Primastana Adnyana; Ida Bagus Windia Adnyana; I Gusti Ngurah Bagus Trilaksana; I Nyoman Suartha; Tjok Gde Oka Pemayun; I Gusti Ngurah Sudisma (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
This study aimed to evaluate the effects of ex-situ habitat transfer on physiological and behavioral stress responses in Indo-Pacific bottlenose dolphins (Tursiops aduncus) and to assess the effectiveness of environmental enrichment in mitigating stress and enhancing welfare. Seven dolphins were monitored across four periods: before transfer, immediately upon arrival at the new facility, after 15 days of adaptation, and following 30 days of environmental enrichment using interactive toys. Parameters measured included neutrophil-to-lymphocyte (N/L) ratio, respiratory rate, frequency of stereotypic behaviors, food intake, social interactions, and compliance with trainer commands. The results demonstrated that habitat transfer induced significant increases in N/L ratio and respiratory rate. A 15-day adaptation period was insufficient to restore physiological and behavioral parameters to baseline levels. However, after 30 days of environmental enrichment, stress indicators improved markedly, with decreased N/L ratios, normalized respiratory rates, reduced stereotypic behaviors, and increased food intake, social interactions, and compliance. These findings underscore the importance of integrating structured environmental enrichment strategies into ex-situ conservation and management programs to support optimal welfare in captive dolphins.